AVALIAÇÃO DA PRODUÇÃO DE BIOMASSA DO FUSTE DE UM CLONE HÍBRIDO DE EUCALIPTO SOB DIFERENTES ESPAÇAMENTOS - Ribeiro, Maria Dolores Dos Santos Barzotto; Jorge, Luiz Alberto Blanco; Mischan, Martha Maria; Santos, André Luis Dos; Ballarin, Adriano Wagner (Universidade Federal de Santa Maria, 2017)
ABSTRACT The use of forests of Eucalyptus has become more expressive in Brazil, mostly because of the excellent production in volumetric terms reached by them and the good characteristics of the obtained wood. The present work was developed to search the best plantations spacings for clonal forests of a interspecific hybrid of Eucalyptus grandis and Eucalyptus urophylla, to maximize the production of the stem biomass per hectare. The data were made available by the company 'Duratex Florestal' and are proceeding from a clonal test at the age of 72 months. The used statistician delineation was the systematic one with continuous quantitative factor, 16 treatments and 40 repetitions, considering that the variation between the treatments was the spacing between the trees and the space between rows was constant with three meters. Along with this arrangement, the vital area per tree was 1,50m2 (6.667 trees per hectare) to 15,75m2 (635 trees per hectare). The highest production volume and stem biomass per hectare occurred in spacing treatments with dense planting - 3x0, 50m, in large spacings (from 9.00 m² per plant life), it was on volume and biomass per tree stem. In this study, it was observed an increase in the weighted basic density of timber to the vital area of 4.95 m² per tree. From this vital area, the basic density remained virtually unchanged.

RESUMO O uso de florestas de Eucalyptus tem se tornado cada vez mais expressivo no Brasil, sobretudo por conta da excelente produção em termos volumétricos por elas alcançadas e pelas boas características da madeira obtida. O presente trabalho teve como objetivo identificar os melhores espaçamentos de plantio para florestas clonais de um híbrido interespecífico de Eucalyptus grandis e Eucalyptus urophylla, de forma a maximizar a produção de biomassa do fuste por hectare buscando a área vital por árvore em um intervalo que favorecesse o crescimento em diâmetro e a formação de madeira de maior densidade básica. Os dados foram disponibilizados pela empresa Duratex Florestal e são provenientes de um teste clonal exploratório de 72 meses de idade. O delineamento estatístico utilizado foi o sistemático com fator quantitativo contínuo, com 16 tratamentos e 40 repetições, considerando que a variação entre os tratamentos foi o espaçamento entre as árvores e a entrelinha possuía um espaçamento constante de três metros. Com este arranjo, o experimento possuiu área vital por árvore variando de 1,50 m2 (6.667 árvores por hectare) até 15,75 m2 (635 árvores por hectare). A maior produção em volume e biomassa do fuste por hectare ocorreu nos tratamentos com espaçamento de plantio adensado - 3 x 0,50 m; nos espaçamentos amplos, a partir de 9,00 m² de área vital por planta, a produção de volume e biomassa do fuste por árvore foi maior. Foi observado um aumento na densidade básica ponderada da madeira até a área vital de 4,95 m² por árvore, a partir desta área vital, a densidade básica se manteve praticamente inalterada.
EVALUATION OF THE BIOMASS PRODUCTION OF THE MAIN STEM OF A HYBRID EUCALYPTUS CLONE UNDER DIFFERENT SPACINGS
Keywords: plantations spacing; Eucalyptus clone; stem biomass; systematic design; espaçamento de plantio; clone de Eucalyptus; biomassa do fuste; delineamento sistemático